A biographical dictionary of civil engineers in Great Britain and Ireland. Vol. 2, - Cross-Rudkin, P. S. M. (Thomas Telford, 2008)
With biographical details of nearly 800 leading civil engineers of the Victorian era, this dictionary includes many that have never been written about until now. It outlines the lives of these engineers and lists the works for which they were responsible, and provides indexes of names and places.